2016
DOI: 10.3366/cor.2016.0084
|View full text |Cite
|
Sign up to set email alerts
|

The use of thebe-passive in academic Englishes: localversusglobal usage in an international language

Abstract: In this paper, we examine the diffusion of a syntactic change in a specialised text type in different World Englishes – in particular, the use of be-passives in academic discourse in nine contact varieties of English and six English as a Native Language (ENL) varieties. The Zürich-parsed International Corpus of English (ICE) makes it possible to retrieve automatically, for the first time, the two variants in the envelope of variation: active transitive constructions and be-passives. We apply regression analysi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
14
0

Year Published

2017
2017
2022
2022

Publication Types

Select...
6
1

Relationship

3
4

Authors

Journals

citations
Cited by 14 publications
(14 citation statements)
references
References 24 publications
0
14
0
Order By: Relevance
“…Previous research has shown that US scientific writing takes the lead in an ongoing change: the decline in the use of passives relative to active transitive clauses (Seoane & Loureiro-Porto 2005; Seoane 2006a, 2006b; Leech et al 2009). Hundt, Schneider, and Seoane (2016) show that regional variety is one of the factors determining the frequency of passives in academic writing, with a divide between American English (AmE), on the one hand, and fourteen (inner and outer circle) varieties of English, on the other. Statistically more significant, however, is the pronounced variation across disciplinary areas, with the soft sciences showing lower proportions of passives than the hard sciences.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Previous research has shown that US scientific writing takes the lead in an ongoing change: the decline in the use of passives relative to active transitive clauses (Seoane & Loureiro-Porto 2005; Seoane 2006a, 2006b; Leech et al 2009). Hundt, Schneider, and Seoane (2016) show that regional variety is one of the factors determining the frequency of passives in academic writing, with a divide between American English (AmE), on the one hand, and fourteen (inner and outer circle) varieties of English, on the other. Statistically more significant, however, is the pronounced variation across disciplinary areas, with the soft sciences showing lower proportions of passives than the hard sciences.…”
Section: Introductionmentioning
confidence: 99%
“…On the basis of automatically retrieved central be -passives and active transitives in several components of the International Corpus of English (ICE), 2 Hundt, Schneider, and Seoane (2016) analyze voice alternation in the academic discourse of six native varieties of English (ENL) and nine contact varieties of English (eight ESL, English as a second language, and one ESD, English as a second dialect). Regression analysis reveals a regional divide between AmE, with the lowest rate of passives, and all other varieties, which tend to be closer to BrE, regardless of whether they are native or contact varieties.…”
Section: Introductionmentioning
confidence: 99%
“…On the whole, the structurally markedly different passive constructions that are due to general processes of second-language acquisition are quite likely to have been edited out in published academic writing. Hundt et al (2016) test for recall of automatically retrieved transitive active and passive constructions and are able to show that such characteristically ESL constructions are very infrequent in the academic part of the ICE corpora.…”
Section: Periphrasticmentioning
confidence: 87%
“…Leech et al 2009) identified regional differences in a shift from passive towards active constructions, which is more pronounced in American English (AmE) than in British English (BrE) academic writing. The question was whether the trend towards greater use of the active voice could also be found in other first-and second-language varieties of English (see Hundt et al 2016). In this paper, we add to previous research by looking into the factors predicting the choice between active and passive.…”
Section: Introductionmentioning
confidence: 92%
See 1 more Smart Citation